The Inter-Agency Committee on Radiation Safety—30 years of international coordination of radiation protection and safety matters. (6th December 2021) - Mundigl, Stefan; Blackburn, Carl; Pinak, Miroslav; Colgan, Tony; Clement, Christopher; Otto, Thomas; Voytchev, Miroslav; Niu, Shengli; Coates, Roger; Guen, Bernard Le; Rannou, Alain; Lazo, Edward; et al.
Abstract: The Inter-Agency Committee on Radiation Safety (IACRS) was constituted in 1990, as a forum for collaboration and coordination between international bodies with regards to radiation safety. It consists today of representatives of eight intergovernmental member organizations (the European Commision, Food and Agriculture Organization, International Atomic Energy Agency (IAEA), International Labour Office, Organisation for Economic Co-operation and Development/ Nuclear Energy Agency (OECD/NEA), Pan American Health Organization, United Nations Scientific Committee on the Effects of Atomic Radiation and the World Health Organization) and five observer non-governmental organizations (International Commission on Radiological Protection, International Commission on Radiation Units & Measurements, International Electrotechnical Commission, International Radiation Protection Association and International Organization for Standardization). The IACRS provides a platform for interaction between these relevant international bodies to contribute to a common understanding of the scientific basis and legal framework for the application of the system of radiation protection, towards global harmonisation of radiation safety standards. The IACRS played a key role in the development of the International Basic Safety Standards (BSS) in 1996 and in its revision in 2014. Further, an IACRS specific Task Group—chaired by the IAEA—fosters the implementation of the BSS in a consistent and coherent manner in all Member States of the United Nations. The IACRS operates via a standing secretariat jointly provided by the IAEA and OECD/NEA and is chaired by one of its member organizations on a rotating basis for periods of about 18 months. This approach has proved to be effective and was the foundation for ensuring continuity of the work of the committee and at the same time allowing a rotating leadership for all member organizations. Currently, the IACRS is chaired by the WHO. The International Radiation Safety Framework under which the IACRS works is structured around four main areas: (a) science; (b) principles; (c) standards; and (d) practice. This paper presents briefly the mandates, roles and functions of the various international bodies that are relevant to the four above mentioned areas of work, discusses how these bodies coordinate their actions and complement each other to enhance radiation protection and safety worldwide and describes their contribution to the achievement of the Sustainable Development Goals. The paper also provides an overview of the main accomplishments of the IACRS since its inception 30 years ago, and an outlook on key challenges for its future activities.